A systematic review on the cultural design process for cultural creative product in China - Yuan, Jing; Abdul Ghafar, Maszura; Azmi, Athira (UiTM Press, 2024)
Lacking of cultural creative product’s (CCP) appeal and innovation are causing low purchasing interest among locals especially in China. There is a need to enhance the product appeal to improve the product purchasing in China. The purpose of this study is to identify what are the best cultural design processes for CCP in China. This desktop study investigates on the current cultural design processes in China, the emotion of cultural design processes for CCP, and the best cultural-emotion design processes characteristics for CCP. This paper uses systematic review to identify topic’s themes, knowledge gaps and approaches towards traditional cultural element, design process and cultural creative products. 29 journals articles were search through Google scholar database between 1992 to 2022. This study found that when traditional connotation elements and creative design were injected into the CCP design processes, these elements could transform and develop CCP into cultural emotion and functional experiences hence, enhance purchasing power for users. The findings of this study would aid local manufacturers rise in sales through instilling connotation features and creative design during cultural design processes in CCP.